(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
There are two general classes of likelihood spaces; each is unmistakable, both subjectively and quantitatively. The principal appropriation is known as thin tail, the second is fat tail. In slight tail disseminations, factual special cases happen yet they don’t convey bizarrely enormous results. In fat-tail conveyances, when critical deviations (Black swans) happen, the results are normally disastrous in nature. Black Swan is an occasion or event that strays past what is regularly expected of a circumstance and that would be very hard to anticipate. Standard deviation is a helpful factual estimation of hazard, if the fundamental resource returns are circulated in a typical manner about the mean. Be that as it may, if the benefit returns go amiss altogether from what might be normal in a slim tail standard deviation is regularly a lacking and poor estimation of all out hazard and can frequently bring about the genuine underestimation of potential misfortunes. VaR is genuinely exact in anticipating little day by day misfortunes with high likelihood; it separates totally in determining enormous calamitous misfortunes that exist in the tail of the dispersion – Black swan occasions.